Examining the Influence of Bureaucratic Culture on Organizational Performance in Public Agencies - Nengsih, Setiyah (Generasi Sains Indonesia, 2024)
This take a look at examines the influence of bureaucratic subculture on organizational performance in public agencies via a combined-methods method. Descriptive facts analysis of survey records exhibits moderate to excessive degrees of hierarchy, formalization, and centralization, indicating the prevalence of bureaucratic norms within the groups. Additionally, organizational performance indicators show wonderful perceptions of effectiveness and employee delight, albeit with room for improvement in performance. The findings underscore the importance of balancing bureaucratic systems with organizational effectiveness, emphasizing the need for adaptability and innovation in public provider delivery.